Current trends in altitude training - Wilber, R. L. (Sports Medicine, 2001)
In recent years endurance athletes have begun to use several novel approaches and modalities for altitude training. These include: I) normobaric hypoxia via nitrogen dilution (hypoxic apartment), 2) supplemental oxygen, 3) hypoxic sleeping devices, and 4) intermittent hypoxic exposure (IRE). A normobaric hypoxic apartment simulates an altitude environment equivalent to approximately 2000 to 3000 m (6560 to 9840 fi). Athletes who use a hypoxic apartment typically "live and sleep high" in the hypoxic apartment for 8 to 18 hours a day, but complete their training at sea level, or approximate sea level conditions. Data from several studies suggest that using a hypoxic apartment in this manner may produce beneficial changes in serum erythropoietin (sEPO), reticulocyte count, and red blood cell (RBC) mass, which in turn may lead to improvements in postaltitude endurance performance. However, other studies have failed to demonstrate significant changes. Supplemental oxygen is used for the purpose of simulating either normoxic (sea level) or hyperoxic conditions during high-intensity workouts conducted at altitude. Use of supplemental oxygen in this manner is a modification of the "high-low" strategy in that athletes live in a natural terrestrial altitude environment but train at "sea level" with the aid of supplemental oxygen. Although limited, scientific data suggest that high-intensity workouts at moderate altitude (1860 m / 6100 ft) and endurance performance at sea level may be enhanced when supplemental oxygen training is utilized over a duration of several weeks. Hypoxic sleeping devices include the Colorado Altitude Training (CAT) HatchTM and Hypoxico Tent SystemTM, both of which are designed to allow athletes to sleep high and train low. The CAT Hatch is a cylindrical hypobaric chamber that can simulate altitudes up to approximately 4575 m / 15,006 ft. The Hypoxico Tent System is a normobaric hypoxic device that simulates elevations up to approximately 4270 m / 14,005 ft. IHE is based on the assumption that brief exposures to hypoxia (1.5-2.0 hrs) are sufficient to stimulate the release of sEPO, and ultimately bring about an increase in RBC concentration. Athletes typically use intermittent hypoxic exposure while at rest, or in conjunction with a training session. ln effect. this allows the athlete to "live low-train high".